Strengthening of the local budget of Lviv region by the non-tax revenues - Chushak-Goloborodko, Anna; Stadnyk, Tetiana (Видавництво Львівської політехніки, 2013)
Abstract – Analyzed the urgent issues of local budget revenues formation of Lviv region. Focused primarily on nontax revenues that represent an additional source of budget revenue formation. Shows the dynamics and structure of nontax revenue in local budget of Lviv region in 2010-2012 in order to identify reserves of their increase.
Keywords: local budget; non-tax revenues; administrative fees and charges; local governments; own revenues; decentralization